Pengaruh Organizational Citizenship Behavior, Employee Engagement dan Budaya Organisasi terhadap Kinerja Pegawai PDAM Tirta Moedal Kota Semarang - Purnamasari, Hilda; Sijabat, Rauly; Indriasari, Ika (Universitas PGRI Semarang, 2025)
This study aims to analyze the influence of organizational citizenship behavior, employee engagement, and organizational culture on the performance of employees at PDAM Tirta Moedal, Semarang City. The data used in this study consists of primary data obtained from questionnaires using a probability sampling technique. The population in this study consists of 106 employees of PDAM Tirta Moedal, Semarang City. The responses from the questionnaires were then subjected to validity tests, reliability tests, normality tests, linearity tests, and heteroscedasticity tests. The data analysis method employed in this study uses multiple linear regression tests with the assistance of SPSS software. The results of the study indicate that organizational citizenship behavior, employee engagement, and organizational culture have a positive effect on employee performance.